Analysis of Lembang Fault Characteristics based on Literatures of Geological Structure, Rock Formation and Peak Ground Acceleration Probabilistic Earthquake Analysis - Totok Doyo Pamungkas; Epon Ningrum (Universitas Pendidikan Indonesia, 2022)
Earthquakes are a very frequent phenomenon, especially in the territory of Indonesia with a lot of compression pressure from the Eurasian and Indian Ocean tectonic plates. The influence of volcanism activity and the southern part of the Java subduction pathway triggers the formation of faults in Java, one of which is the Lembang fault. How is the geological history process structurally and the calculation of the maximum peak ground acceleration (PGA) to determine the characteristics of the Lembang fault? In this study, the focus is on a literature review with descriptive methods with the aim of collecting reference data information on studies to find out more about the characteristics of the Lembang fault. Based on the results of the literacy study that was collected and the interpretation of the structure that has been carried out, it can be stated that the characteristics of the Lembang fault are very complex through six sections. The majority are normal faults with strike-slip fault variations in several parts. The maximum peak ground acceleration probabilistic earthquake analysis on the Lembang fault depends on the distance and trajectory of the fault and the source of the earthquake and is on the type of soft or hard rock formation. Areas that have the highest maximum ground movement acceleration are in the North and East Bandung areas.